Immune-related signature of periodontitis and Alzheimer’s disease linkage - Jin, Jieqi; Guang, Mengkai; Li, Simin; Liu, Yong; Zhang, Liwei; Zhang, Bo; Cheng, Menglin; Schmalz, Gerhard; Huang, Xiaofeng (Frontiers in Genetics, 2023)
Background: Periodontits (PD) and Alzheimer's disease (AD) are both associated with ageing and clinical studies increasingly evidence their association. However, specific mechanisms underlying this association remain undeciphered, and immune-related processes are purported to play a signifcant role.The accrual of publically available transcriptomic datasets permits secondary analysis and the application of data-mining and bioinformatic tools for biological discovery. Aim: The present study aimed to leverage publically available transcriptomic datasets and databases, and apply a series of bioinformatic analysis to identify a robust signature of immune-related signature of PD and AD linkage. Methods: We downloaded gene-expresssion data pertaining PD and AD and identified crosstalk genes. We constructed a protein-protein network analysis, applied immune cell enrichment analysis, and predicted crosstalk immune-related genes and infiltrating immune cells. Next, we applied consisent cluster analysis and performed immune cell bias analysis, followed by LASSO regression to select biomarker immunerelated genes. Results: The results showed a 3 gene set comprising of DUSP14, F13A1 and SELE as a robust immune-related signature. Macrophages M2 and NKT, B-cells, CD4+ memory T-cells and CD8+ naive T-cells emerged as key immune cells linking PD with AD. Conclusion: Candidate immunerelated biomarker genes and immune cells central to the assocation of PD with AD were identified, and merit investigation in experimental and clinical research.